Development of quantitative real-time PCR and digital droplet-PCR assays for rapid and early detection of the spoilage yeasts Saccharomycopsis fibuligera and Wickerhamomyces anomalus in bread. (February 2022) - Cremonesi, Paola; Garofalo, Cristiana; Picozzi, Claudia; Castiglioni, Bianca; Mangieri, Nicola; Milanović, Vesna; Osimani, Andrea; Aquilanti, Lucia
Abstract: In the present study, for the first time, high sensitive quantitative polymerase chain reaction (qPCR) and digital droplet polymerase chain reaction (ddPCR) assays were developed to detect and quantify total eumycetes with potential application in several food matrices and to specifically determine the level of contamination by Saccharomycopsis fibuligera and Wickerhamomyces anomalus cells directly in bread. Among the candidate target genes used to develop the assays, car1 gene was chosen to detect the two spoilage yeasts S. fibuligera and W. anomalus . The specificity of the PCR assays was tested using purified genomic DNA from 36 bacterial and fungal strains. The sensitivity of the assays was defined by using tenfold serial dilutions of genomic DNA starting from 10 6 cfu/mL to 1 cfu/mL of S. fibuligera and W. anomalus . Validation of the assays was achieved by enumeration of S. fibuligera and W. anomalus DNA copies from samples of artificially contaminated bread homogenates detecting up to 10 cfu/mL (0.06 ± 0.01 copies/μL) of W. anomalus by using ddPCR. In conclusion, the developed qPCR and ddPCR assays demonstrate strong performance in the early detection of S. fibuligera and W. anomalus in bread, representing promising tools for applying high-throughput approaches to regularly monitor bread quality. Highlights: Bread can be spoiled by "chalk molds", such as S. fibuligera and W. anomalus. The bakery industry needs reliable methods for the early detection of chalk molds. QPCR and ddPCR assays have been developed for chalk molds quantification in bread. Novel qPCR and ddPCR assays show high specificity and sensitivity in bread. These methods may enable producers to apply preventive actions against chalk molds.